HUBUNGAN ANTARA TEGANGAN PERMUKAAN RESIN AKRILIK DAN JUMLAH PELIKEL YANG TERADSORPSI - Dyah Irnawati; Siti Sunarintyas (Faculty of Dentistry, Universitas Indonesia, 2015)
The aim of this research is to investigate the correlation of acrylic resins surface tension (chemial, heat, and microwave activated) on the amount of adsorbed pellicle on the acrylic surfaces. Sixty samples (10x10x2 mm)  were made of chemical activated (Hilon, England), heat activated (Stellon, England), and microwave activated (Acron MC, Japan) acrylic resins. Contact angle (surface tension of acrylic resins and saliva (5 treatment groups, n=3) an acrylic resins and aquadest (control group, n=5) were measured by photographing method. The samples from treatment groups were contacted with saliva for 1 hour, 2, 3, 4 and 5 hours and the protein concentration were measured by Bradford method. The data were analyzed by analysis of variants, LSD, and correlations. The results showed that: (1) acrylic resins type influenced the surface tensions (p<0,01), (2) the contact duration influenced the pellicle concentrations (p<0,01), and (3) there was not any correlation between acrylic resins surface tensions and the concentration of adsorbed pellicle (p>0,05). It was concluded that there is not any correlation between acrylic resins surface tension and the amount of adsorbed pellicle.